Clinical evaluation of the therapeutic efficacy and tolerability of piperacillin. - Lutz, B (1982)
The efficacy and tolerance of parenterally administered piperacillin were evaluated in 50 adult patients hospitalized with systemic and urinary tract infections. Dosage for 46 patients was 4 to 12 g daily and for 4 patients, 16 to 24 g daily; in each case divided doses were given every 4 to 6 h. The duration of treatment for most patients was 5 to 10 days. Of the 50 patients, 45 (90%) were considered cured, and 57 (89%) of the 64 pathogens isolated were eradicated by piperacillin treatment. Side effects, reported by 12 patients, were mild to moderate in degree and consisted of vein irritation, thrombophlebitis, pain at the injection site, and diarrhea, Piperacillin appears to be a highly effective antibiotic for treating infections caused by susceptible gram-positive and gram-negative microorganisms.